Biomaterials for High-Throughput Stem Cell Culture - Lan Levengood, Sheeny; L. Murphy, William (Current Stem Cell Research & Therapy, 2010)
A cell's microenvironment plays a primary role in defining cell fate during tissue development, physiological function, and pathological dysfunction. Understanding the key components and interactions within these microenvironments is critical for effective use of stem cells for disease modeling and therapeutic applications. Yet cell microenvironments are difficult to study, as there are tens or hundreds of parameters that can influence cell behavior simultaneously. Additionally, parameters such as cell-cell interactions, cell-ECM interactions, cell shape, soluble signals, and mechanical forces vary dynamically in 3-dimensional space and time. The number of relevant experimental conditions in these cell-based biological systems quickly becomes intractable using standard experimental platforms and techniques. A new set of strategies involving high-throughput experimental formats and 3-dimensional culture is required to achieve significant progress in understanding and exploiting stem cell biology. This mini-review describes bioengineering approaches that are enabling for high-throughput stem cell culture, screening and analysis.
Keywords: growth factors